2015
DOI: 10.1002/ange.201411625
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Water Oxidation by a Dinuclear Copper Complex in a Neutral Aqueous Solution

Abstract: ,h as been investigated. This catalyst exhibits high reactivity and stability towards water oxidation in neutral aqueous solutions.DFT calculations suggest that the O À Ob ond formation takes place by an intramolecular direct coupling mechanism rather than by an ucleophilic attacko fw ater on the high-oxidation-state Cu IV =Omoiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 47 publications
(12 reference statements)
6
36
0
Order By: Relevance
“…The first example of a homogeneous copper-based WOC in neutral solutions was reported by Zhang et al, [62] detailing the electrocatalytic activity of a dinuclear copper complex [Cu 2 (BPMAN)(μ-OH)] 3 + (Cu-18, Figure 13, BPMAN = 2,7-[bis(2pyridylmethyl)aminomethyl]-1,8-naphthyridine) in pH 7 phosphate buffer. CV measurements showed a quasi-reversible redox wave originating from a Cu II /Cu I at E 1/2 = 0.02 V (vs. NHE) that demonstrated a pH dependence of approximately 59 mV per pH unit, suggesting a 1e À /1H + process.…”
Section: Copper-based Wocs For Electrocatalysis In Neutral Solutionmentioning
confidence: 99%
“…The first example of a homogeneous copper-based WOC in neutral solutions was reported by Zhang et al, [62] detailing the electrocatalytic activity of a dinuclear copper complex [Cu 2 (BPMAN)(μ-OH)] 3 + (Cu-18, Figure 13, BPMAN = 2,7-[bis(2pyridylmethyl)aminomethyl]-1,8-naphthyridine) in pH 7 phosphate buffer. CV measurements showed a quasi-reversible redox wave originating from a Cu II /Cu I at E 1/2 = 0.02 V (vs. NHE) that demonstrated a pH dependence of approximately 59 mV per pH unit, suggesting a 1e À /1H + process.…”
Section: Copper-based Wocs For Electrocatalysis In Neutral Solutionmentioning
confidence: 99%
“…Therefore, the development of efficient electrocatalysts for water oxidation is an avenue to improve the competence of fuel generation technology. Great efforts and progresses have been made recently in exploring molecular complexes and solid materials that are active for electrocatalytic or photocatalytic OER . In particular, since the development of Co−Pi catalyst by Nocera and co‐workers, widespread attentions have been focused for the development of first‐row transition metal‐oxides‐based electrocatalysts such as Co, Ni, Cu, Mn and Fe for the ultimate development of photoelectrochemical solar water splitting cell ,,.…”
Section: Figurementioning
confidence: 99%
“…CV of 36 showed two irreversible oxidation waves at 0.87 V and 1.41 V in NaPi buffer at pH 7.0, which were assigned to the oxidation of Ni(II) to Ni(III) and the further oxidation of Ni(III) to Ni(IV). Compared with other homogeneous transition metal-based WOCs (500-800 mV)[27,112,126,127], a relatively low overpotential was exhibited by 36. To verify that the electrocatalysis by 36 is a homogeneous reaction, a series of control experiments were performed: (1) Catalytic current decreased as a result of multiple CV scans and became constant finally, this is in contrast to the observed feature for heterogeneous Ni-based catalysts[122,124].…”
mentioning
confidence: 83%
“…After a long-term electrolysis of up to 4 h, no spectra changes were observed and no heterogeneity in catalyst was detected, giving evidence that 39 is an efficient and stable catalyst in eletrocatalytic water oxidation. Further DFT calculations revealed that O-O bond formation prefers an intramolecular direct coupling of O-O bond between two Cu III centers[127].…”
mentioning
confidence: 99%